A flexible electrode based on polycarbonate gold nano array, sensor and application

CN117129535BActive Publication Date: 2026-10-27NANTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311010464.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-11
Publication Date
2026-10-27
Estimated Expiration
2043-08-11

AI Technical Summary

Benefits of technology

[0024]1.本发明可以在较短时间(60s)实现汗液乳酸的快速检测。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117129535B_ABST
    Figure CN117129535B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of wearable electrochemical analysis and detection, and discloses a flexible electrode based on polycarbonate gold nano array, a sensor and application. The flexible electrode takes a flexible polycarbonate porous film with nano-scale conical membrane holes as a substrate, gold nanoparticles are deposited on the first side, the second side and the surface of the membrane holes of the substrate to form a conductive layer, and enzyme solution chitosan gel is embedded in the conical membrane holes with the deposited gold nanoparticles on the surface and the conductive layer on the first side of the substrate. The flexible electrode has high electrochemical performance and sensitivity, excellent mechanical flexibility and good biocompatibility, and can be applied to real-time detection of sweat lactic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wearable electrochemical analysis and detection technology, and specifically relates to a flexible electrode, sensor and application based on polycarbonate gold nanoarray. Background Technology

[0002] Over the past decade, point-of-care diagnostics (POC) has seen significant development. The possibility of rapid diagnosis, testing, and treatment means that healthcare services are no longer confined to hospitals or clinics. Wearable, non-invasive testing, in particular, can provide real-time and continuous data on various health-related biomarkers, avoiding the pain and risks associated with traditional invasive diagnostics and making it easier to use in the home.

[0003] Among non-invasive human body fluids, sweat plays a crucial role. Compared to tests for tears, saliva, and urine, sweat testing truly balances non-invasiveness, comfort, and the ease of obtaining samples continuously. Sweat contains various electrolytes and metabolites, providing rich physiological information; for example, detecting elevated chloride levels in sweat can help detect cystic fibrosis in infants. Among the many components of sweat, lactic acid is considered an important biomarker due to its association with several diseases, including electrolyte imbalances, dehydration, and acidosis.

[0004] To date, various wearable sensing platforms using different electrode materials have been developed to detect lactic acid in sweat. In 2014, a textile-based sensor was developed for semi-quantitative colorimetric detection of sweat lactic acid. Later, the development of flexible electronics technology made quantitative detection of sweat lactic acid possible. For example, Andreu et al. combined paper microfluidic channels with gold nanoparticles to form a sensor for detecting sweat lactic acid content and sweat volume. Researchers used smartphones to derive colorimetric signals and quantify the sweat lactic acid content. However, the accuracy of colorimetric methods is easily affected by ambient light, and the reproducibility of the detection results is poor, hindering their practical application. Besides colorimetric analysis, electrochemical analysis is one of the most commonly used methods for detecting lactic acid in sweat, offering higher sensitivity, a linear dynamic range (LDR), and a lower limit of detection (LOD). For example, Tamoghna's team used lactate oxidase (LOC)... X Modified screen-printed electrodes were used to detect lactic acid in sweat, with a limit of observation (LOD) of 350 nM and a linear dynamic range (LDR) of 0-15 mM. While the detection limit was low, its linear dynamic range was insufficient to cover the expected range of lactic acid in sweat during exercise, potentially leading to inaccurate results for high-concentration lactic acid. With the development of nanomaterials and electronic technology, gold nanoarray electrodes have been constructed with high specific surface area and strong electrode activity, enabling accurate, rapid, and highly sensitive detection of lactic acid in sweat. Furthermore, combining these gold nanoarray electrodes with flexible substrates allows for their application in wearable real-time detection devices. Summary of the Invention

[0005] In view of this, the present invention aims to provide a flexible electrode, a flexible sensor and its application based on a polycarbonate film, wherein the flexible sensor has high electrochemical performance and sensitivity, excellent mechanical flexibility and good biocompatibility.

[0006] The technical solution provided by this invention is as follows:

[0007] A flexible electrode based on a polycarbonate gold nanoarray, comprising:

[0008] The substrate is a flexible polycarbonate film with nanoscale conical membrane pores, the conical membrane pores penetrating the flexible polycarbonate film, the large end of the conical membrane pores corresponding to the first side of the flexible polycarbonate film, and the small end of the conical membrane pores corresponding to the second side of the flexible polycarbonate film.

[0009] A conductive layer is formed by depositing gold nanoparticles on a first side, a second side, and the surface of the membrane pores of the substrate.

[0010] An enzyme solution chitosan gel is disposed on a conductive layer on the first side of the substrate and within a conical membrane pore on which gold nanoparticles are deposited; the enzyme solution chitosan gel contains lactate oxidase.

[0011] Furthermore, the diameter of the large end of the conical membrane pore is 220 nm, and the diameter of the small end of the conical membrane pore is 130 nm.

[0012] This invention also provides a method for preparing a flexible electrode, comprising the following steps:

[0013] S1. A nanoscale conical membrane pore is formed on a flexible polycarbonate film using an etching process, penetrating the flexible polycarbonate film;

[0014] S2. Deposit gold nanoparticles on the surface of the flexible polycarbonate film obtained in step S1 to obtain a flexible polycarbonate film with a conductive layer on the first side, the second side and the surface of the conical membrane pore.

[0015] S3. After mixing the lactate oxidase solution and chitosan gel evenly, drop the mixture onto the first side and the conical membrane pores of the flexible polycarbonate film obtained in step S2, and incubate it in a refrigerator at 4°C for 6 hours to obtain a flexible electrode.

[0016] Furthermore, the concentration of the lactate oxidase solution is 50 U / mL, the concentration of the chitosan gel is 2 wt%, and the volume ratio of the lactate oxidase solution to the chitosan gel is 1:1.

[0017] The present invention also provides a flexible sensor based on a polycarbonate gold nanoarray, the flexible sensor comprising, from top to bottom, a first flexible support structure, the aforementioned flexible electrode, and a second flexible support structure; a first side of the flexible electrode is close to the first flexible support structure; a second side of the flexible electrode is close to the second flexible support structure; the first flexible support structure has a cavity penetrating the first flexible support structure, the cavity being a reaction pool for the reaction liquid.

[0018] Furthermore, both the first flexible support structure and the second flexible support structure are polydimethylsiloxane layers.

[0019] Furthermore, the chamber is cylindrical in shape.

[0020] The present invention also provides the application of the above-mentioned flexible sensor in the detection of lactic acid in sweat.

[0021] Furthermore, the first flexible support structure of the flexible sensor is in contact with the object being detected, and the reaction liquid is sweat.

[0022] Specifically, this flexible sensor utilizes the confined space of nanoporous electrodes to embed lactate oxidase. When sweat comes into contact with the lactate oxidase embedded in the gel within the nanochannels, the resulting hydrogen peroxide is detected by the nanoarray electrodes, thus quantifying the lactic acid content. The key advantage of this method is its ability to rapidly quantify sweat lactic acid content in a short time, overcoming the limitations of most current wearable lactic acid sensors, such as high detection limits and narrow detection ranges. Furthermore, it is reusable multiple times, making it more economical and environmentally friendly.

[0023] The technical solution of the present invention has the following advantages compared with the prior art:

[0024] 1. This invention can achieve rapid detection of lactic acid in sweat in a short time (60s).

[0025] 2. The present invention can achieve a low detection limit (40 nM) and a wide detection range (0-35 mM).

[0026] 3. This invention enables rapid on-site detection of wearable sweat lactic acid, and can be used as a new method for detecting sweat lactic acid.

[0027] This flexible electrode is easy to fabricate, inexpensive, and possesses high electrochemical performance and sensitivity (detection limit of 40 nM), excellent mechanical flexibility, and good biocompatibility. It can be widely used in portable analytical devices for early clinical diagnosis, real-time disease monitoring, and human health monitoring. Attached Figure Description

[0028] The technical solution and its beneficial effects of the present invention will become apparent from the following detailed description of specific embodiments in conjunction with the accompanying drawings.

[0029] Figure 1 A schematic diagram illustrating the fabrication process of the flexible sensor device based on polycarbonate gold nanoarray provided by the present invention;

[0030] Figure 2 This is a diagram of the etching apparatus (U-shaped electrolytic cell) used in an embodiment of the present invention;

[0031] Figure 3 Characterization images of the flexible electrode in Example 1 of this invention: (AB) etched PC nanoporous membrane; (C) SEM image of nano-Au / PC; (D) elemental mapping image of nano-Au / PC; (E) EDX spectrum.

[0032] Figure 4 The following is a graph showing the test results of Test Example 1 of the present invention; wherein, (A) is the CV graph of flexible electrodes with different pore sizes in potassium ferricyanide containing 10mM, and (B) is the dual Y-axis graph of oxidation peak current and peak potential difference.

[0033] Figure 5 The current response of a flexible polycarbonate film with a conductive layer to an equivalent standard lactic acid solution under different lactate oxidase concentrations is shown in Example 2.

[0034] Figure 6 The current response of the flexible electrode to the equivalent standard lactic acid solution at different initial potentials in Test Example 3 is shown in the figure.

[0035] Figure 7 The CV and impedance spectra of the flexible electrode in Test Example 4 in 10 mM potassium ferricyanide are shown.

[0036] Figure 8 The current response and calibration diagram of the flexible electrode in Test Example 5 to 2.5 mM incremental lactic acid in PBS are shown.

[0037] Figure 9 The measured sweat it graph obtained from test example 6;

[0038] Figure 10 The graph shows the test results for Test Example 7. Figure 10 A shows the test results of sweat concentration from 6 volunteers. Figure 10 B is a comparison graph showing the test results of this test case with the lactic acid content in sweat detected by high performance liquid chromatography (HPLC). Detailed Implementation

[0039] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0040] Example 1

[0041] This embodiment provides a method for fabricating a flexible electrode based on a polycarbonate film, such as... Figure 1 As shown, the specific steps are as follows:

[0042] S1. Unidirectional etching yields a porous polycarbonate film:

[0043] Place the polycarbonate film in, as Figure 2 In the etching apparatus (U-shaped electrolytic cell) shown, 15 mL of 6M NaOH solution was added to one side, and 15 mL of stop solution, containing a mixture of 1M formic acid and 1M KCl, was added to the other side. Under a 50°C water bath condition, the current was monitored using an IRT (Inertial Measurement System) device. When the current reached approximately 1.2e-7 A, another 15 mL of stop solution was added to each side of the U-shaped electrolytic cell. This yielded a porous polycarbonate film with a macropore diameter of approximately 220 nm and a micropore diameter of approximately 40 nm. Figure 3 A and Figure 3 B are scanning electron microscope images of the macropore end and micropore end of the polycarbonate porous film, respectively.

[0044] S2. Electrodeposited gold nanoparticles:

[0045] The polycarbonate porous film obtained in step S2 was irradiated on both sides for 30 min each in a 254 nm UV box, then immersed in 50 mM EDC NHS solution for 30 min, then immersed in 1 mM chloroauric acid solution for 90 min, then transferred to 0.1 mM sodium borohydride solution for 3 min, then immersed in 0.5 M potassium thiocyanate solution for ultrasonic treatment for 3 min, and finally immersed in a gold plating solution in a 60 °C water bath for 60 min. The gold plating solution contained 0.625 M formaldehyde solution, 0.127 M sodium sulfite and 7.9 mM anhydrous sodium gold sulfite solution to obtain sample 1, which is a flexible polycarbonate film with gold nanoarray. Figure 3 C is the scanning electron microscope (SEM) image of sample 1, showing the formation of a gold nanoarray structure. Figure 3 D represents the elemental mapping result of sample 1, where Au comes from the deposited gold nanoarray, and C and O come from the polycarbonate substrate. Figure 3 E is the EDX spectrum of sample 1, showing the distribution of Au and C,O elements, which further reflects the uniform deposition of gold nanoparticles.

[0046] S3. Fabrication of flexible electrodes:

[0047] A 5 U / ml lactate oxidase solution and a 20 wt% chitosan solution were mixed at a volume ratio of 1:1 and dropped onto a gold nanoarray electrode to fill the electrode surface and conical pores. The mixture was then incubated at 4°C for 6 hours to obtain a flexible electrode.

[0048] Example 2

[0049] This embodiment provides a method for fabricating a flexible electrode based on a polycarbonate nanoarray, the specific steps of which are as follows:

[0050] S1. Unidirectional etching yields a porous polycarbonate film:

[0051] Place the polycarbonate film in, as Figure 2 In the etching apparatus (U-shaped electrolytic cell) shown, 15 mL of 6M NaOH solution was added to one side, and 15 mL of stop solution, containing a mixture of 1M formic acid and 1M KCl, was added to the other side. Under a 50°C water bath, the current was monitored using an IRT (internal temperature range) device. When the current reached approximately 2e⁻⁷ A, another 15 mL of stop solution was added to each side of the U-shaped electrolytic cell. This yielded a polycarbonate porous film with a macropore diameter of approximately 220 nm and a micropore diameter of approximately 80 nm.

[0052] S2. Electrodeposited gold nanoparticles:

[0053] The polycarbonate porous film obtained in step S2 was irradiated on both sides for 30 min each in a 254 nm UV box, then immersed in 50 mM EDC NHS solution for 30 min, then immersed in 1 mM chloroauric acid solution for 90 min, then transferred to 0.1 mM sodium borohydride solution for 3 min, then immersed in 0.5 M potassium thiocyanate solution for ultrasonic treatment for 3 min, and finally immersed in a gold plating solution in a 60 °C water bath for 60 min. The gold plating solution contained 0.625 M formaldehyde solution, 0.127 M sodium sulfite and 7.9 mM anhydrous sodium gold sulfite solution to obtain a flexible polycarbonate film with gold nanoarrays.

[0054] S3. Fabrication of flexible electrodes:

[0055] A 25 U / ml lactate oxidase solution and a 20 wt% chitosan solution were mixed at a volume ratio of 1:1 and dropped onto a gold nanoarray electrode to fill the electrode surface and conical pores. The mixture was then incubated at 4°C for 6 hours to obtain a flexible electrode.

[0056] Example 3

[0057] This embodiment provides a method for fabricating a flexible electrode based on a polycarbonate nanoarray, the specific steps of which are as follows:

[0058] S1. Unidirectional etching yields a porous polycarbonate film:

[0059] Place the polycarbonate film in, as Figure 1 In the etching apparatus (U-shaped electrolytic cell) shown, 15 mL of 6M NaOH solution was added to one side, and 15 mL of stop solution, containing a mixture of 1M formic acid and 1M KCl, was added to the other side. Under a 50°C water bath, the current was monitored using an IRT (internal temperature range) device. When the current reached approximately 8e⁻⁷ A, another 15 mL of stop solution was added to each side of the U-shaped electrolytic cell. This yielded a polycarbonate porous film with a macropore diameter of approximately 220 nm and a micropore diameter of approximately 130 nm.

[0060] S2. Electrodeposited gold nanoparticles:

[0061] The polycarbonate porous film obtained in step S2 was irradiated on both sides for 30 min each in a 254 nm UV box, then immersed in 50 mM EDC NHS solution for 30 min, then immersed in 1 mM chloroauric acid solution for 90 min, then transferred to 0.1 mM sodium borohydride solution for 3 min, then immersed in 0.5 M potassium thiocyanate solution for ultrasonic treatment for 3 min, and finally immersed in a gold plating solution in a 60 °C water bath for 60 min. The gold plating solution contained 0.625 M formaldehyde solution, 0.127 M sodium sulfite and 7.9 mM anhydrous sodium gold sulfite solution to obtain a flexible polycarbonate film with gold nanoarrays.

[0062] S3. Fabrication of flexible electrodes:

[0063] A 50 U / ml lactate oxidase solution and a 20 wt% chitosan solution were mixed at a volume ratio of 1:1 and dropped onto a gold nanoarray electrode to fill the electrode surface and conical pores. The mixture was then incubated at 4°C for 6 hours to obtain a flexible electrode.

[0064] Example 4

[0065] This embodiment provides a method for fabricating a flexible nanoarray sensor based on polycarbonate nanoarrays, the specific steps of which are as follows:

[0066] S1. Unidirectional etching yields a porous polycarbonate film:

[0067] Place the polycarbonate film in, as Figure 1 In the etching apparatus (U-shaped electrolytic cell) shown, 15 mL of 6M NaOH solution was added to one side, and 15 mL of stop solution, containing a mixture of 1M formic acid and 1M KCl, was added to the other side. Under a 50°C water bath, the current was monitored using an IRT (internal temperature range) device. When the current reached approximately 4e⁻⁶ A, another 15 mL of stop solution was added to each side of the U-shaped electrolytic cell. This yielded a polycarbonate porous film with a macropore diameter of approximately 220 nm and a micropore diameter of approximately 180 nm.

[0068] S2. Electrodeposited gold nanoparticles:

[0069] The polycarbonate porous film obtained in step S2 was irradiated on both sides for 30 min each in a 254 nm UV box, then immersed in 50 mM EDC NHS solution for 30 min, then immersed in 1 mM chloroauric acid solution for 90 min, then transferred to 0.1 mM sodium borohydride solution for 3 min, then immersed in 0.5 M potassium thiocyanate solution for ultrasonic treatment for 3 min, and finally immersed in a gold plating solution in a 60 °C water bath for 60 min. The gold plating solution contained 0.625 M formaldehyde solution, 0.127 M sodium sulfite and 7.9 mM anhydrous sodium gold sulfite solution to obtain a flexible polycarbonate film with gold nanoarrays.

[0070] S3. Fabrication of flexible electrodes:

[0071] A 75 U / ml lactate oxidase solution and a 20 wt% chitosan solution were mixed at a volume ratio of 1:1 and dropped onto a gold nanoarray electrode to fill the electrode surface and conical pores. The mixture was then incubated in a 4°C refrigerator for 6 hours to obtain a flexible electrode.

[0072] Example 5

[0073] A method for fabricating a flexible sensor based on a polycarbonate gold nanoarray includes the following steps:

[0074] S1. Construct the first flexible support structure:

[0075] PDMS prepolymer and curing agent were mixed evenly at a ratio of 10:1 and poured into a prepared 3D mold of the first flexible support structure. The mold of the first flexible support structure was 1.5 cm long and wide, and 0.3 cm high, containing a cylinder with a diameter of 0.5 cm and a height of 0.3 cm in the center. The mold containing the PDMS was placed in a vacuum drying oven for 30 ± 5 minutes to remove air bubbles, and then cured and peeled off to obtain the first flexible support structure. The first flexible support structure has a cavity that extends through it, and the cavity serves as a reaction tank for the reaction liquid.

[0076] S2. Prepare the second flexible support structure according to the method in step S1, except that the 3D mold of the second flexible support structure does not include the cylinder with a central diameter of 0.5 cm and a height of 0.3 cm. Place the flexible electrode on the second support structure, place the first support structure on the flexible electrode, and solidify to obtain a flexible sensor based on a polycarbonate nanoarray.

[0077] Test Example 1

[0078] The flexible polycarbonate film with gold nanoarrays prepared in step S2 of Examples 1-4 was measured using an electrochemical workstation in 10 mmol / L potassium ferricyanide, and its cyclic voltammogram, redox peak current, and potential difference dual Y-axis plot were also measured. Figure 4 As shown in A and B.

[0079] according to Figure 4 As can be seen from A, the electrode redox peak current gradually increases with the increase of the pore size at the small pore end of the polycarbonate porous film.

[0080] according to Figure 4 As shown in Figure B, the redox peak current of the electrode with an aperture of 130 nm reaches its maximum value, and the peak-to-peak potential difference is also relatively small. Therefore, 130 nm can be selected as the optimal aperture for fabricating flexible sensors.

[0081] Test Example 2

[0082] Lactate oxidase solutions with concentrations of 5 U / mL, 25 U / mL, 50 U / mL, and 75 U / mL, respectively, and 20 wt% chitosan solution were mixed at a volume ratio of 1:1 and added dropwise onto the flexible polycarbonate film with gold nanoarrays prepared in step S2 of Example 3, filling the electrode surface and conical pores. The film was incubated at 4°C for 6 hours. 30 μL of a 7.5 mM lactic acid solution was added dropwise to react with the film, and the current response is shown in the figure. Figure 5 As shown, the lactate reaction current is the largest at an enzyme concentration of 50 U / mL. Therefore, a lactate oxidase concentration of 50 U / mL was selected as the optimal concentration for preparing the flexible sensor.

[0083] Test Example 3

[0084] Initial potentials of 0.6V, 0.65V, 0.7V, 0.75V, and 0.8V were set respectively, and the flexible electrode prepared in step S3 of Example 3 was subjected to iterative testing using an electrochemical workstation. Figure 6 As shown, the reaction current of the electrode to lactic acid increases with the increase of the initial potential of the IT test between 0.6V and 0.7V. However, when the initial potential is further increased, the change in reaction current is negligible. Considering that a higher initial potential is accompanied by more side reactions, an initial potential of 0.7V for the IT test is selected as the detection potential of the flexible sensor.

[0085] Test Example 4

[0086] The polycarbonate porous film prepared in step S1 of Example 3, the flexible polycarbonate film with gold nanoarray prepared in step S2, and the flexible electrode prepared in step S3 were used to measure their cyclic voltammograms in 10 mmol / L potassium ferricyanide using an electrochemical workstation. Figure 7 A) and impedance spectrum ( Figure 7 B). Figure 7 A shows that the flexible electrode has the highest redox peak and the smallest peak-to-peak potential difference, indicating that the flexible electrode has the best conductivity. Figure 7 The electrochemical impedance spectroscopy shown in B further verifies this result.

[0087] Test Example 5

[0088] The current response of the flexible electrode prepared in step S3 of Example 3 to 2.5 mM incremental lactic acid (lactic acid standards of different concentrations) in PBS is shown in the graph. Figure 8 A) and calibration chart ( Figure 8 B); Figure 8 As shown in Figure A, the response current increases accordingly with the continuous addition of lactic acid, reflecting a good electrochemical sensing capability.

[0089] Figure 8 B shows a linear relationship between the response current and the lactic acid concentration in the range of 0 mM to 35 mM, with a correlation coefficient of 0.998.

[0090] Test Example 6

[0091] The flexible sensor prepared in Example 5 was attached to the arm of a volunteer in motion. A three-electrode detection system was constructed using the flexible sensor as the working electrode, a silver / silver chloride electrode as the reference electrode, and a platinum wire as the counter electrode. The resulting image is shown in Figure 1. Figure 9 As shown, at the instant sweat contacts the surface of the flexible electrode through the chamber, the current increases rapidly, and then drops to a stable plateau in the shortest possible time. Based on this current, combined with... Figure 8 B can assess the concentration level of lactic acid in sweat.

[0092] Test Example 7

[0093] The flexible sensor prepared in Example 5 was used on the arms of six volunteers of different genders and ages to continuously detect the concentration of lactic acid in their sweat. The results are as follows: Figure 10 As shown in Figure A. Sweat samples were then collected from volunteers undergoing the same exercise, and the lactic acid content in the sweat was detected using high-performance liquid chromatography (HPLC). The results were compared to obtain the following information: Figure 10 The Bland-Altman plot shown in Figure B indicates good consistency between the two quantitative detection methods.

[0094] The above description is merely an exemplary embodiment of the present invention and does not limit the scope of patent protection of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the scope of patent protection of the present invention.

Claims

1. A flexible electrode based on a polycarbonate gold nanoarray, characterized in that, include: The substrate is a flexible polycarbonate porous film with nanoscale conical membrane pores, wherein the conical membrane pores penetrate the flexible polycarbonate porous film, the large pore end of the conical membrane pores corresponds to a first side of the flexible polycarbonate porous film, and the small pore end of the conical membrane pores corresponds to a second side of the flexible polycarbonate porous film; the diameter of the large pore end of the conical membrane pores is 220 nm, and the diameter of the small pore end of the conical membrane pores is 130 nm; A conductive layer is formed by depositing gold nanoparticles on a first side, a second side, and the surface of the membrane pores of the substrate; the conductive layer is used to detect hydrogen peroxide produced by lactate oxidase catalyzing the decomposition of lactate, so as to quantify the lactate content. An enzyme solution chitosan gel is disposed on a conductive layer on the first side of the substrate and within a conical membrane pore on which gold nanoparticles are deposited; the enzyme solution chitosan gel contains lactate oxidase; The enzyme solution-chitosan gel was prepared using the following method: After the lactate oxidase solution and chitosan gel were mixed evenly, they were dropped onto the first side of the substrate with the conductive layer and into the conical membrane pores to fill the electrode surface and the conical pores. The mixture was then incubated in a refrigerator at 4°C for 6 hours.

2. A method for fabricating a flexible electrode based on a polycarbonate gold nanoarray as described in claim 1, characterized in that, Includes the following steps: S1. A nanoscale conical membrane pore is formed on a flexible polycarbonate film using an etching process, penetrating the flexible polycarbonate film; S2. Deposit gold nanoparticles on the surface of the flexible polycarbonate film obtained in step S1 to obtain a flexible polycarbonate film with a conductive layer on the first side, the second side and the surface of the conical membrane pore. S3. After mixing the lactate oxidase solution and chitosan gel evenly, drop the mixture onto the first side and the conical membrane pores of the flexible polycarbonate film obtained in step S2, filling the electrode surface and conical pores. Incubate the mixture in a refrigerator at 4°C for 6 hours to obtain a flexible electrode.

3. The preparation method according to claim 2, characterized in that, The concentration of the lactate oxidase solution is 50 U / mL, the concentration of the chitosan gel is 2wt%, and the volume ratio of the lactate oxidase solution to the chitosan gel is 1:

1.

4. A flexible sensor based on a polycarbonate gold nanoarray, characterized in that, The flexible sensor comprises, from top to bottom, a first flexible support structure, the flexible electrode as described in claim 1, and a second flexible support structure; The first side of the flexible electrode is close to the first flexible support structure; The second side of the flexible electrode is close to the second flexible support structure; The first flexible support structure has a cavity that extends through the first flexible support structure, and the cavity is a reaction pool for the reaction liquid.

5. The flexible sensor according to claim 4, characterized in that, Both the first flexible support structure and the second flexible support structure are polydimethylsiloxane layers.

6. The flexible sensor according to claim 4, characterized in that, The chamber is cylindrical in shape.

7. The application of the flexible sensor according to claim 4 in the detection of lactic acid in sweat for non-diagnostic purposes.

8. The application according to claim 7, characterized in that, The first flexible support structure of the flexible sensor is in contact with the object being detected, and the reaction liquid is sweat.

Citation Information

Patent Citations

  • Adhesive tape-based electrochemical sweat sensor

    CN110672687A

  • Functionalized porous polymer nanocomposites

    US20160104554A1